2007
DOI: 10.2478/v10001-007-0017-1
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Mercury Vapors in Dental Workers in Poland

Abstract: Objectives:The study aimed at assessing the effect of low-level exposure to mercury (Hg) vapor from amalgam fi llings among dental surgery staff in the city of Łódź, Poland. Materials and Methods: The study group was composed of 51 workers (mean age, 39.25±11.05 years) employed in dental surgeries; the control group comprised 16 white-collar workers (mean age, 40.05±10.57 years) of the Nofer Institute of Occupational Medicine, Łódź, who had no or a few amalgam dental fi llings. Total urine mercury (Hg-U) conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
1
9
0
3
Order By: Relevance
“…In our study, there is a statistically significant positive correlation between duration of exposure and both U-Hg and B-Hg (Table 2), this is in resemblance with the results of Herber et al, 1988;Ritchie et al, 2004;Trzcinka-Ochocka et al, 2007; however, it did not agree with Kobal et al (2004); in their study of retired miners, they reported a significant negative correlation between U-Hg concentration and duration of time after exposure.…”
Section: U-hgsupporting
confidence: 83%
See 2 more Smart Citations
“…In our study, there is a statistically significant positive correlation between duration of exposure and both U-Hg and B-Hg (Table 2), this is in resemblance with the results of Herber et al, 1988;Ritchie et al, 2004;Trzcinka-Ochocka et al, 2007; however, it did not agree with Kobal et al (2004); in their study of retired miners, they reported a significant negative correlation between U-Hg concentration and duration of time after exposure.…”
Section: U-hgsupporting
confidence: 83%
“…However, Trzcinka-Ochocka et al (2007) in their study aimed at assessing the effect of exposure to mercury (Hg) vapor from amalgam fillings among dental surgery staff in a city of Poland. They reported that there was no statistically significant differences in the mean of urinary Hg concentrations between the study and control groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schütz and Elinder 34) noted urinary excretion of α 1 -microglobulin (HC) above the cut-off level in 10% of the investigated population with cadmium in urine (Cd-U) concentrations about 1 µg/g creatinine. The results obtained recently by Noonan et al 35) and Trzcinka-Ochocka et al 36) revealed that the urinary excretion of early biomarkers of kidney dysfunction can be increased at cadmium levels in urine of about 2.0 µg/ g creatinine.…”
Section: Cadmiummentioning
confidence: 91%
“…Uap merkuri dapat terhirup atau terabsorbsi melalui alveolus di paru-paru sampai 80%. [9][10] Sistem saraf merupakan target utama dari toksisitas metal, terutama senyawa metal organik. Misalnya metal merkuri, karena mempunyai sifat larut dalam lemak (lipid soluble), secara mudah melewati blood brain barrier dan masuk ke sistem saraf.…”
Section: Pendahuluanunclassified